Potensi Mikroorganisme dalam Makanan Fermentasi Lokal Indonesia sebagai Pangan Fungsional - Muttaqin, Salwa Zainum; Napitupulu, Alexis Rachel Maria Rosauli; Mamangkey, Jendri (Mahesa Research Center, 2025)
This study aims to examine the potential of microorganisms in Indonesian local fermented foods as functional food through a qualitative descriptive approach using literature review. Traditional fermented foods such as tempeh, oncom, shrimp paste (terasi), brem, lemea, kabuto, poteng reket, and swansrai are cultural products rich in various microorganisms, including Rhizopus sp., Neurospora sitophila, Lactobacillus sp., and Saccharomyces cerevisiae. These microorganisms play essential roles in the fermentation process, producing bioactive compounds such as lactic acid, probiotics, proteolytic enzymes, and B-complex vitamins that provide physiological benefits beyond basic nutritional functions. Fermentation not only enhances nutritional value and food safety but also offers positive health effects, including maintaining gut microbiota balance, boosting immunity, reducing the risk of degenerative diseases, and serving as natural antimicrobials and antioxidants. Data were collected from national and international scientific literature published in the last ten years. The findings indicate that Indonesian local fermented foods hold great potential to be developed into functional foods based on local wisdom. With appropriate utilization of natural microorganisms, traditional Indonesian foods can contribute to food security, public health, and the sustainable development of the functional food industry.